A Health Profile of African Immigrant Men in the United States - Nipher Malika; Lisa R. Roberts; Carlos A. Casiano; Susanne Montgomery (Elsevier, 2023)
African immigrants (AI) are the fastest growing group of immigrants to the U.S. however, their health and health practices remains poorly characterized. Thus, this study aimed to describe the health profile of this under-described U.S. population. In order to contextualize their health profiles, we compared AI (n=95) to other U.S. Black populations, namely African Americans (AA, n=271) and Caribbean American (CA, n=203) immigrants. We used cross-sectional survey data from a prostate cancer health study with 569 Black adult male participants, ages 21 years or older. Demographic characteristics were compared using Chi-square tests and prevalence ratios, and prevalence odds ratios (POR) were estimated for AIs compared to AA and CA immigrants using a log-binomial regression model. Results revealed that AI exhibited significantly lower prevalence of asthma and diabetes, when compared to AA and CA immigrants. Furthermore, AI reported lower consumption of alcohol than AA (POR, 0.43, 95%CI 0.24, 0.75) and lower smoking prevalence than AA (POR, 0.19, 95%CI 0.05, 0.70) and CA immigrants (POR, 0.21, 95%CI 0.05, 0.76). Additionally, AI reported significantly lower medical mistrust than CA (POR, 0.51, 95%CI 0.26, 0.95), significantly low financial strain than CAs immigrants (POR, 1.66, 95%CI 1.00, 2.75) and significantly higher levels of religious coping than both AA (POR, 2.43, 95%CI 1.43, 4.12) and CA immigrant men (POR, 1.78, 95%CI 1.03, 3.08). This study further supports emerging evidence that Blacks in the U.S. are not a monolithic group and that it is necessary to assess the Black subgroups separately. In addition, as one of the fastest growing immigrant populations, it is critical for future research to understand African immigrant's health needs and its correlates.